Baby says - Steptoe, John, 1950-1989. (New York : Lothrop, Lee & Shepard Books, 1988)
A baby and big brother figure out how to get along.
Keywords: Brothers -- Fiction; Babies -- Fiction; African Americans -- Fiction; Brothers -- Juvenile fiction; Infants -- Juvenile fiction; African Americans -- Juvenile fiction